Schädigung und Lebensdauer von Nickelbasislegierungen unter thermisch-mechanischer Ermüdungsbeanspruchung bei verschiedenen Phasenlagen - Guth, Stefan (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2016)
This work considers the behaviour of two nickel-base alloys under thermo-mechanical fatigue loading with varying phase angles between mechanical strain and temperature. The investigations focus on the characterisation of microstructures and damage mechanisms as a function of the phase angle. Based on the results, a life prediction model is proposed.